Spoligotyping of Mycobacterium africanum, Burkina Faso - Gomgnimbou, Michel K. (Centers for Disease Control and Prevention, 2012)
Using Ziehl-Neelsen–positive slides collected from tuberculosis diagnostic centers in Burkina Faso, we showed that 20% of 80 spoligotyping-positive DNA samples had a characteristic Mycobacterium africanum–specific genomic signature. This result suggests that M. africanum is still present in Burkina Faso at almost the same prevalence as 15–20 years ago.